Terminal differentiation of human granulosa cells as luteinization is reversed by activin-A through silencing of Jnk pathway - Bildik, Gamze; Akin, Nazli; Esmaeilian, Yashar; Hela, Francesko; Yildiz, Ceren Sultan; Iltumur, Ece; İncir, Said; Karahuseyinoglu, Sercin; Yakin, Kayhan; Oktem, Ozgur (Cell Death Discovery, 2020)
Molecular mechanisms underlying luteinization (terminal differentiation of granulosa and theca cells after ovulation) and luteolysis (demise of corpus luteum) are poorly understood in human ovary. Here we report that activin-A, after binding to its cognate receptors induces a functional luteolytic state and reverses luteinization phenotype by downregulating the expression of the steroidogenic enzymes, LH receptor and VEGF and reducing estradiol (E2) progesterone (P4) production and upregulating FSH receptor and cyclin D1 expression in human primary luteinized granulosa cells. Further, this action of activin-A involves downregulation of JNK signaling pathway and is opposite to that of human chorionic gonadotropin (hCG), which acts as a luteotropic hormone and improves luteal function through the activation of JNK pathway in the same cell type. Reversal of luteinization phenotype in luteal granulosa cells by activin-A potentially makes this hormone an attractive candidate for use under certain clinical situations, where induction of luteolysis and rapid reduction of endogenous sex steroid levels are beneficial such as ovarian hyperstimulation syndrome (OHSS), in which the ovaries hyper-respond to gonadotropin stimulation by producing too many growing follicles along with development of ascites, pleural effusion, and hemo-concentrations as a result of increased vascular permeability and leakage of intravascular volume into third spaces. Our work unveils a previously undefined role for activin-A and JNK signaling pathway in human corpus luteum biology, that might have a direct clinical impact in assisted reproductive technologies.